PERSEPSI FOLLOWERS GENERASI Z TERHADAP PESAN KOMUNIKASI EDUKASI KESEHATAN MENTAL PADA AKUN INSTAGRAM @SOCIALCONNECT.ID - Iga Cilvia Arisman; Flora Meliana Siahaan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the increasing use of Instagram as a medium for disseminating information including mental health education which is widely accessed by Generation Z. The study aims to describe and analyze the perceptions held by Generation Z followers regarding mental health education communication messages on the @socialconnect.id Instagram account. It employs Joseph A. DeVito’s Perception Theory encompassing the stages of selection, organization, and interpretation as its primary framework, supported by Uses and Gratifications Theory to explain media usage motives. The study utilizes a constructivist paradigm with a descriptive qualitative approach. Data were gathered through in-depth interviews with two informants, observation of content on the @socialconnect.id Instagram account, and document analysis, followed by processing using the interactive analysis model developed by Miles, Huberman, and Saldana. The results indicate that followers actively select content aligned with their information needs and emotional states, organize information by linking it to their existing experiences and knowledge, and interpret the messages as beneficial education that influences their perspectives and behaviors regarding mental health. The study concludes that the @socialconnect.id Instagram account serves as a health communication medium capable of fostering understanding and raising mental health awareness among Generation Z followers through the delivery of relevant educational messages, even though users maintain a critical stance toward information obtained via social media.